MUTU KERTAS DARI PULP BATANG KELAPA SAWIT THE PAPER QUALITY OF STEM PALM PULP - Hendri Candra Jepri; Faizah ' Hamzah; Rudianda ' Sulaeman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Paper is acrucial part of human life. The high demand of paper must be balanced with the availability of materials. One source of lignocellulosic usage still limited is oil palm. The purpose of this research is to determine the characteristics of paper made from the pulp of oil palm trunk. This study is conducted experimentally using a completely randomized design (CRD) with 3 treatments, K1 (paper from pulp palm trunks the base), K2 (paper from pulp oil palm trunk middle) and K3 (paper from pulp oil palm trunk end portion) with 5 replications. The data are statistically analyzed using Analysis of Variance (ANOVA), if F count is greater than or equal to F table then continued with DNMRT test at 5% level. The results shows that treatment of oil palm trunk influences on pulp yield, tearing strength, tensile strength, folding, moisture content of the paper and no real effect on the bursting strength and brightness of the paper. Yield pulp produced from oil palm trunk ranges from 37.57-41.22%. Tearing strength of paper pulp produced from oil palm trunk ranges from 8.0-8.6 mNm2/g. Tensile strength ​​of the paper produced from the pulp of palm trunks flashing ranges from 73.5-80.0 Nm/g. Bursting strength of paper from pulp stem flashing produced from oil ranges from 4.9-5.3 kPam2/g. Folding paper pulp produced from oil palm trunk ranges between 413-588. Brightness of the paper produced from the pulp of oil palm trunk ranges from 83.81-86.03%ISO. Moisture content of the paper produced from the pulp of oil palm trunk ranges from 6.30-7.09%. Keywords: Paper, pulp, stem palm, and paper quality.